Recovery of kidney function after acute kidney injury in the elderly: a systematic review and meta-analysis - Schmitt, Roland; Coca, Steven; Kanbay, Mehmet; Tinetti, Mary E; Cantley, Lloyd G; Parikh, Chirag R (American journal of kidney diseases, 2008)
The prevalence of elderly individuals continues to increase over time, as does the incidence of acute kidney injury (AKI). However, it is not known whether age is an important prognostic predictor for renal recovery after an episode of AKI. Systematic review of MEDLINE and EMBASE databases and meta-analysis of pooled data using random-effect models. Adults with AKI, not including kidney transplant recipients. Studies published in English between 2000 and 2007 were eligible for this analysis if they met the following inclusion criteria: (1) clear definition of AKI and recovery of kidney function, (2) assessment of kidney function recovery as the primary or secondary outcome, and (3) participant age reported. We contacted the investigators of studies and requested data for recovery of kidney function by patient age. Patient age of 65 years and older and younger than 65 years. Recovery of kidney function defined as independence from dialysis therapy, decrease in serum creatinine level to less than a defined threshold, or return to baseline kidney function. We obtained data for recovery of kidney function by age from 17 studies of patients with AKI. Overall, 31.3% of surviving elderly patients did not recover kidney function compared with 26% of younger patients (pooled relative risk, 1.28, 95% confidence interval, 1.06 to 1.55; P < 0.05). The increased risk of nonrecovery in the elderly remained greater in several subgroups examined through sensitivity analyses, including those stratified by type of dialysis support, time of assessment of recovery (short versus long term), and definition of renal recovery. There was significant heterogeneity among studies with respect to comorbid factors, definition of AKI, and study design. There is impaired recovery of kidney function after AKI in aged individuals. Future studies should be cognizant of "age" as a potential effect modifier in the prognosis after AKI, and clinical trials should focus on improving outcomes in the elderly cohort.